Pressure Induced Phase Transition of ZrN and HfN: A First Principles Study (Journal of Atomic and Molecular Sciences, 2013)
The structural, elastic, and electronic properties of zirconium nitride (ZrN)and hafnium nitride (HfN) are investigated by first principles calculation with densityfunctional theory. The obtained cubic NaCl structure is energetically the most stablestructure at ambient pressure. A pressure induced structural phase transition fromB1 to B2 phase is predicted. The estimated superconducting transition temperature $(T_c)$ of ZrN and HfN are 9.17 K and 8.66 K respectively. As pressure increases, thesuperconducting transition temperature also increases.
Keywords: electronic structure; elastic properties; structural phase transitions; superconducting transition temperature.